Importance of growth hormone for the induction of hepatic low density lipoprotein receptors. - Rudling, M (1992)
This investigation was undertaken to determine the possible role of growth hormone (GH) in the hormonal regulation of hepatic low density lipoprotein (LDL) receptor expression. Treatment of normal rats with estrogen (ethynylestradiol, 5 mg/kg per day) increased the number of hepatic LDL receptors, and the LDL receptor mRNA levels were increased 2.4-fold. However, when hypophysectomized rats were treated with estrogen, the hepatic LDL receptor number and the mRNA levels only increased slightly. Treatment with GH was important to restore the induction of hepatic LDL receptors in hypophysectomized estrogen-treated rats. Further, the hypocholesterolemic effect of estrogen was abolished in hypophysectomized rats, and GH reversed this effect. To assess the effect of GH in humans, hepatic LDL receptor binding activity was determined in liver biopsy specimens from gallstone patients pretreated with GH (12 international units/day) prior to operation. GH administration induced hepatic LDL receptors approximately 2-fold, and this was accompanied by a 25% decrease in serum cholesterol. The LDL receptor stimulation caused by GH treatment was of similar magnitude as that observed upon 3 weeks of treatment with an established hypolipidemic drug (pravastatin or simvastatin). The data show that GH has an important role in the regulation of hepatic LDL receptors and suggest that GH secretion may be important for the control of plasma LDL levels in humans.